The effects of Angiotensin-Converting-Enzyme Inhibitor (Captopril) on Gentamicin Nephrotoxicity in rats - Al-Attiyah, Zainab M; Al-Ani, Imad Matloub Dally; Abdul-Kareem, Humam N.; Matlop, Enas I. (Research and Reviews (Shastri Educational Trust®), 2013)
This study was designed to investigate the effects of captopril on gentamicin nephrotoxicity. Six groups of male Wister rats “15 rats each” were used. Group “C”, was given 1ml of normal saline, group “G25” was injected with a single dose of GM (25mg/Kg/day), group “G50” was injected with a single dose of GM (50mg/Kg/day), group “Cp2” was given a single oral dose of captopril (2mg/day), group “Cp2+G25” was injected with a single dose of GM (25mg/Kg/day) and a single oral dose of captopril (2mg/day), group “Cp2+G50” was injected with a single dose of GM (50mg/Kg/day) and a single oral dose of captopril (2mg/day). Treatment continued daily for 15 days; analysis was performed on days 5, 10 and 15. Blood urea nitrogen and serum creatinine levels were significantly elevated on the 5 day and continued to increase throughout the duration of the experiment; there was a gradual decrease in the creatinine clearance level, starting from the 5th day of treatment, which was related to the duration and dosage used in the GM treated rats. The administration of captopril progressively reduced the functional deteriorations induced by GM. It is concluded that captopril reduces GMinduced renal damage, suggesting protective effect of captopril against GM nephrotoxicity.